SIFAT KAYU LAPIS PINUS DENGAN BEBERAPA MACAM KETEBALAN - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
Experimental plywood  panels   were  made  from   bolts  of  tapped  and  untapped Pinus  merkusii  trees  obtained   from East Java.  The  bolts  were rotary peeled   into  veneers  of  1.5   mm,  2.0  mm  and 3.0  mm  thick.  Veneer  of  1.5 mm  was  exclusively   used  as face  veneer  and  others  for  core. Plywood   panels   were  glued  with  urea  formaldehyde resin. Plywood were made  with 5 thickness variation (5.00 mm, 6.00 mm, 7.5 mm, 9.0 mm  and 12.00  mm).                                    The  physical   and  mechanical  properties   of  all panels   were  tested  according   to  the ASTM   standard,  and  bonding strength   of  plywood  was  tested   according  to  Indonesian,   Japanese  (JAS)  and  Germany (DIN)  standards. The  results indicated that  there  is no  significant   difference   in  moisture   content,   density   of  plywood  made  tapped  and  untapped pine   wood.                                                                                                                 Mechanical  properties   of  plywood (bending  strength, tensile  strength   and  compression   strength)   were significant difference   made of tapped  and untapped  pine  wood  also vice versa with  its thickness variation.Bonding  of glue  of plywood  there  is no significant  difference made  tapped  and untapped  pine  wood. Only plywood which tested  its  bonding  strength   using  Germany   standard  indicated  significant  shear strength  of plywood  with  thick ness 5.00 mm  is better  than that  of  the 6.00  mm  thickness.Modulus  of rupture  and compression  strength  of  tapped pine plywood are better than the untapped one.